Dengue Fever Disease Prevention education in the Rifahiyatul Bilad Baturrahim in Jambi City - Yusmahendra, Devi; Lestari, Vina Dwi; Mawarti, Indah; Sari, Putri Irwanti; Yusnilawati, Yusnilwati; Meinarisa, Meinarisa (Jurusan Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2023)
Dengue fever is a deadly disease that attacks children and adults today. In Indonesia, dengue fever is still a health problem because there are still many areas where it is endemic. Dengue fever or DHF is a disease transmitted through mosquitoes that occurs in tropical and subtropical areas of the world. Common symptoms of dengue fever are high fever and flu-like symptoms. Meanwhile, in severe dengue fever, this condition can cause serious bleeding, a sudden drop in blood pressure (shock) and even death. Millions of cases of dengue hemorrhagic fever infection occur throughout the world every year. Dengue fever occurs most often in Southeast Asia, the western Pacific islands, Latin America and Africa. But now the disease has spread to new areas, including local outbreaks in Europe and the southern United States. The best way to prevent infection is to avoid mosquito bites and take steps to reduce mosquito populations. Dengue hemorrhagic fever (DHF) is still a problem for most Indonesian people. Concerns about contracting diseases that originate from mosquito bites increase when the rainy season arrives. Early detection and late treatment result in an increase in cases ending in death.Keywords: Education, Prevention, DHF Mosquito